ANALISIS INTERAKSI SISWA DAN ORANG TUA YANG BEKERJA DI SMAN 1 MEMPAWAH - Apriani, Heni (Jurnal Pendidikan Sosiologi dan Humaniora, 2019)
This study aims to know the role of interaction between students and their parents who work at SMAN 1 Mempawah. This research is conducted according to descriptive qualitative method. The technique used to collecting the data are direct observation, direct communication and documentary studies, while the instrumen are observasi, inteview and documentation. The analysis of this research presented according to descriptive qualitative by 10 participants that consisting of 2 people in each 5 families. The results showed that the interaction between students and their parents in social contact and communication are well established. The kids kiss their parents’ hand before go to school, and using their phone to communicate to their parents